Atrial fibrillation in athletes - Mascia, G.; Perrotta, L.; Galanti, G.; Padeletti, L. (International Journal of Sports Medicine, 2013)
Many studies have shown a relationship between long-term endurance sport practice and atrial fibrillation. Inflammation, anatomic remodelling, alterations in the autonomic system and neurohormonal activation are all possible explanations for the increased prevalence of this arrhythmia in athletes. Atrial fibrillation may determine disabling symptoms like palpitations and impaired physical performance, compromising eligibility for competitive activities, but exclusion from sport is not necessary for all athletes. Limited data are available on drug therapy and recently ablation resulted to be a particularly attractive option for young athletes with paroxysmal atrial fibrillation. The purpose of this review is to discuss mechanisms, clinical features, management of atrial fibrillation in competitive athletes, including criteria for eligibility and disqualification in sport practice